Molecular modelling of the emergence of azole resistance in Mycosphaerella graminicola. - Jonathan G L Mullins; Josie E Parker; Hans J Cools; Roberto C Togawa; John A Lucas; Bart A Fraaije; Diane E Kelly; Steven L Kelly (PLoS ONE)
A structural rationale for recent emergence of azole (imidazole and triazole) resistance associated with CYP51 mutations in the wheat pathogen Mycosphaerella graminicola is presented, attained by homology modelling of the wild type protein and 13 variant proteins. The novel molecular models of M. graminicola CYP51 are based on multiple homologues, individually identified for each variant, rather than using a single structural scaffold, providing a robust structure-function rationale for the binding of azoles, including important fungal specific regions for which no structural information is available. The wild type binding pocket reveals specific residues in close proximity to the bound azole molecules that are subject to alteration in the variants. This implicates azole ligands as important agents exerting selection on specific regions bordering the pocket, that become the focus of genetic mutation events, leading to reduced sensitivity to that group of related compounds. Collectively, the models account for several observed functional effects of specific alterations, including loss of triadimenol sensitivity in the Y137F variant, lower sensitivity to tebuconazole of I381V variants and increased resistance to prochloraz of V136A variants. Deletion of Y459 and G460, which brings about removal of that entire section of beta turn from the vicinity of the binding pocket, confers resistance to tebuconazole and epoxiconazole, but sensitivity to prochloraz in variants carrying a combination of A379G I381V ΔY459/G460. Measurements of binding pocket volume proved useful in assessment of scope for general resistance to azoles by virtue of their accommodation without bonding interaction, particularly when combined with analysis of change in positions of key amino acids. It is possible to predict the likely binding orientation of an azole molecule in any of the variant CYPs, providing potential for an in silico screening system and reliable predictive approach to assess the probability of particular variants exhibiting resistance to particular azole fungicides.